The Effects of Knowledge Management, Digital Leadership and Organizational Culture on Employee Performance - Muis, Indra (Siber Journal of Advanced Multidisciplinary, 2025)
This research article is titled "The Effects of Knowledge Management, Digital Leadership, and Organizational Culture on Employee Performance." The purpose of the study was to explore the implementation of knowledge management, digital leadership, organizational culture, and their impact on employee performance. Additionally, the research aimed to determine the influence of the independent variables—knowledge management, digital leadership, and organizational culture—on the dependent variable, which is employee performance. A quantitative research method was employed, with a sample of 138 employees from State Vocational School Number 5 Banjarmasin, selected through simple random sampling. The data analysis was done using SEM PLS version 4. The results show that neither knowledge management nor digital leadership do not have a significant effect on employee performance. Organizational culture, however, has a positive and significant relationship with employee performance. Therefore, it is crucial for school leaders to encourage the teachers and employees to apply the core values, create and open and transparent communication among them, work as a team, innovate and provide space for teachers and employees to adapt to change so as to improve the performance of employees and teachers such as increase efficiency and productivity, innovative work behavior, high sense of responsibility and adapt to change.